Solutions to handle wellbore instability in Vietsovpetro - Pham Van Hieu (Petrovietnam Journal, 2019)
This paper analyses the causes of wellbore instability from the process of drilling 250 wells on offshore fields of Vietsovpetro (with different trajectory, drilling muds and deviation). On that basis, the author proposes solutions to handle the condition of wellbore instability, e.g. reaming and back reaming with high-viscosity sweep, mud condition, increasing of mud weight in allowable mud weight window. The research also shows the appraisal of drilling method’s influence on the duration of wellbore stability helps reduce well problems and accidents during the drilling process.